HLA‐C and KIR combined genotype as new response marker for HBeAg‐positive chronic hepatitis B patients treated with interferon‐based combination therapy. Issue 8 (4th March 2016) - Stelma, F.; Jansen, L.; Sinnige, M. J.; van Dort, K. A.; Takkenberg, R. B.; Janssen, H. L. A.; Reesink, H. W.; Kootstra, N. A.
Summary: Current treatment for chronic hepatitis B infection (CHB) consists of interferon‐based therapy. However, for unknown reasons, a large proportion of patients with CHB do not respond to this treatment. Hence, there is a pressing need to establish response markers to select patients who will benefit from therapy and to spare potential nonresponders from unnecessary side effects of antiviral therapy. Here, we assessed whether HLA‐C and KIR genotypes were associated with treatment outcome for CHB. Twelve SNPs in or near the HLA‐C gene were genotyped in 86 CHB patients (41 HBeAg positive; 45 HBeAg negative) treated with peginterferon alfa‐2a + adefovir. Genotyping of killer immunoglobin‐like receptors (KIRs) was performed by SSP‐PCR. One SNP in HLA‐C (rs2308557) was significantly associated with combined response in HBeAg‐positive CHB patients ( P = 0.003). This SNP is linked to the HLA‐C group C1 or C2 classification, which controls KIR binding. The combination of KIR2DL1 with its ligand HLA‐C2 was observed significantly more often in HBeAg‐positive patients with a combined response (13/14) than in nonresponders (11/27, P = 0.001). Patients with the KIR2DL1/C2 genotype had significantly higher baseline ALT levels (136 vs 50 U/L, P = 0.002) than patients without this combination. Furthermore, KIR2DL1‐C2 predicted response independent of HBV genotype and ALT at baseline. HLA‐C and KIR genotype is strongly associated with response in HBeAg‐positive CHB patients treated with interferon‐based therapy. In combination with other known response markers, HLA‐C/KIR genotype could enable the selection of patients more likely to respond to interferon‐based therapy.